2011
DOI: 10.1182/blood-2009-11-254490
|View full text |Cite
|
Sign up to set email alerts
|

CCR7 is involved in the migration of neutrophils to lymph nodes

Abstract: Increasing evidence suggests that neutrophils may participate in the regulation of adaptive immune responses, and can reach draining lymph nodes and crossprime naive T cells. The aim of this study was to identify the mechanism(s) involved in the migration of neutrophils to the draining lymph nodes. We demonstrate that a subpopulation of human and mouse neutrophils express CCR7. CCR7 is rapidly expressed at the membrane upon stimulation. In vitro, stimulated human neutrophils migrate in response to the CCR7 lig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
184
3
3

Year Published

2011
2011
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 196 publications
(198 citation statements)
references
References 43 publications
8
184
3
3
Order By: Relevance
“…It has recently been shown that CCR7-mediated signals may also have a role for migration of natural killer cells and neutrophils. 27,28 Furthermore, it is largely unknown where the chemoattractant CCL21 mainly exerts its effects after i.m. administration: at the injection site or in afferent lymphatic vessels/secondary lymphatic tissue.…”
Section: Discussionmentioning
confidence: 99%
“…It has recently been shown that CCR7-mediated signals may also have a role for migration of natural killer cells and neutrophils. 27,28 Furthermore, it is largely unknown where the chemoattractant CCL21 mainly exerts its effects after i.m. administration: at the injection site or in afferent lymphatic vessels/secondary lymphatic tissue.…”
Section: Discussionmentioning
confidence: 99%
“…In confocal microscopic studies neutrophils migrating with fluorescently labeled pathogen were observed in draining lymph vessels [1] and lymph nodes [21]. Moreover, the chemokine receptor CCR7 has been identified as a key player in directing neutrophil migration from the interstitium to the draining lymph nodes [6].…”
Section: Interaction With Other Immune Cellsmentioning
confidence: 99%
“…Increased levels of CCR7 have been found in a number of tumor types, one of which is breast cancer [35][36][37]. As expression of CCR7 is reportedly correlated with lymphatic metastasis and poor prognosis in breast cancers, it could be a good therapeutic target in breast cancer therapy [38].…”
Section: Discussionmentioning
confidence: 99%